Learning style preferences among pre-clinical medical students in a public university in Pahang - Jamani, Nurjasmine Aida; Abd. Aziz, Karimah Hanim; Che Abd. Karim, Hanis Syazana; Nizar, Fatimah Azzahra; Dzulkarnain, Husna Najihah; Azimi, Muhammad Irham (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Educational experts affirm that students prefer various type of learning preference. It is known that the learning style preferences vary among medical students worldwide. Knowing the types will help medical educators to improve their way of conveying lectures and teaching in a more effective learning environment. This study aims to describe the learning style preferences of pre-clinical medical students and the association with their socio-demography. This is a cross sectional study done among Year 1 and Year 2 pre-clinical year medical students in a public university in Kuantan Pahang. Medical students who fulfilled the inclusion and exclusion criteria were recruited using systematic random sampling. A validated learning style questionnaire (VARK) was used to assess their learning style. Descriptive statistics and bivariable analysis was used using SPSS version 23. A total of 166 pre-clinical year medical students participated in this study. The mean age was 21.3 (0.84). Majority of them were Malays (98.2%) and females (69.9%). Most of the students preferred unimodal learning style (80.0%) with the most preferred learning style preferences being kinaesthetic (39.1%). Bivariable analysis showed female students preferred kinesthetic learning style compared to male students (p=0.03). In this study, majority of the pre-clinical year medical students preferred ‘life-like’ learning experience in their study. Hence, we recommend that medical educators to be more aware of the varieties of learning style preferences in order to improve the quality of teaching and learning experiences.